2022
DOI: 10.1002/ajim.23413
|View full text |Cite
|
Sign up to set email alerts
|

Serum per‐ and polyfluoroalkyl substance concentrations in four municipal US fire departments

Abstract: Background Firefighters have occupational and environmental exposures to per‐ and polyfluoroalkyl substances (PFAS). The goal of this study was to compare serum PFAS concentrations across multiple United States fire departments to National Health and Nutrition Examination Survey (NHANES) participants. Methods Nine serum PFAS were compared in 290 firefighters from four municipal fire departments (coded A–D) and three NHANES participants matched to each firefighter on sex, ethnicity, age, and PFAS collection yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…As for the firefighter data, the dust samples provide a perspective of what PFAS firefighters may be exposed to during day‐to‐day operations in the fire station but do not account for exposures associated with firefighting activities. Firefighters' PFOS and PFHxS serum levels were, in general, higher than the median NHANES population data and similar to the levels observed in populations exposed through water contamination 32,33 . Because the levels measured in air and dust at fire stations are comparable to those measured in residential settings, firefighters are likely to be exposed to PFAS during firefighting activities.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…As for the firefighter data, the dust samples provide a perspective of what PFAS firefighters may be exposed to during day‐to‐day operations in the fire station but do not account for exposures associated with firefighting activities. Firefighters' PFOS and PFHxS serum levels were, in general, higher than the median NHANES population data and similar to the levels observed in populations exposed through water contamination 32,33 . Because the levels measured in air and dust at fire stations are comparable to those measured in residential settings, firefighters are likely to be exposed to PFAS during firefighting activities.…”
Section: Discussionsupporting
confidence: 51%
“…Similar patterns were observed in studies with measured serum PFAS levels. Ski waxers were observed to have PFAS serum levels similar to populations exposed to PFAS through contaminated water 32,33 . Our analysis shows that air concentrations of PFDA, PFOA, PFNA, and PFDoDA in ski waxing facilities can exceed occupational indoor air screening levels calculated for this review (Figures 1A, 2A, and 6A).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[4][5][6][7] Firefighters could be particularly vulnerable to these exposures, given their high level of exposures. [8][9][10] Research among career (full-time, salaried) firefighters in the USA has shown that pregnancies to working firefighters were more than twice as likely to result in self-reported pregnancy loss compared with non-firefighters. 1 However, exposures vary by firefighter type because of differences in time at fires, combustion products, activities and equipment used.…”
Section: Introductionmentioning
confidence: 99%
“…Some potential occupational exposures (air pollutants, perfluoroalkyl and polyfluoroalkyl substances (PFAS), and high temperatures) have also been associated with adverse reproductive outcomes among non-firefighters 4–7. Firefighters could be particularly vulnerable to these exposures, given their high level of exposures 8–10…”
Section: Introductionmentioning
confidence: 99%